2014
DOI: 10.1007/s00167-014-3423-5
|View full text |Cite
|
Sign up to set email alerts
|

All-inside suture device is superior to meniscal arrows in meniscal repair: a prospective randomized multicenter clinical trial with 2-year follow-up

Abstract: PurposeMultiple techniques and implants are available for all-inside meniscal repair, but the knowledge about their failure rates and functional outcome is still incomplete. The hypothesis was that there might be differences between meniscal arrows and suture devices regarding reoperation rates and functional outcome. Thereby, the aim of this study was to compare clinical results following repair with the Biofix® arrows or the FasT-Fix® suture devices.MethodsIn this RCT, 46 patients were treated either by Biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The studies were subsequently split in half to determine significance by chi-square. Studies 2,16,22,24,30,36,40,42 with an average or median follow-up duration of <30 months (53%; n = 8) had significantly lower rates of failure than studies 8,23,31,34,35,37,39 with an average or median follow-up duration of >30 months (47%; n = 7) ( P = .016) (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were subsequently split in half to determine significance by chi-square. Studies 2,16,22,24,30,36,40,42 with an average or median follow-up duration of <30 months (53%; n = 8) had significantly lower rates of failure than studies 8,23,31,34,35,37,39 with an average or median follow-up duration of >30 months (47%; n = 7) ( P = .016) (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies included in this review were retrospective or prospective case series. Specifically, 1 study 23 was level 1 evidence, 4 studies 24,35,36,40 were level 3, and 10 studies ∥ were level 4. The MCMS average was 54.4 ± 12 (range, 39-78), with the majority falling in the “fair” range (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, all-inside repair may represent a more heterogeneous technique and may not accurately reflect the most recent generation of all-inside devices. Clinical results may be improving concurrently with improvements to all-inside devices, 22 and this may subject our study to bias and overestimation of the failure rates of all-inside repairs. The American Journal of Sports Medicine Further, studies included without technique randomization are subject to selection bias for repair type.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the arrow group had a significantly higher relative risk of reoperation (3.6 times; 95% CI, 1.1-11.5), but functional outcomes were comparable at mean 2 years' follow-up. 26 However, longer-term outcome data have shown high failure rates with the use of the suture anchor systems. For example, Solheim et al evaluated outcomes in 82 patients at a minimum of 7 years and demonstrated a 48% failure rate with the use of the RapidLoc system.…”
Section: Discussionmentioning
confidence: 99%